Gate-enhanced broadband photodetection based on Cd3As2/graphene Dirac heterojunctions - Liao, Xin; Xu, Chang; Fan, Zi-Pu; Lan, Ying-Ying; Li, Na; Chu, Chun-Guang; Wang, An-Qi; Sun, Dong; Liao, Zhi-Min (Applied physics letters, 2023)
Dirac semimetals are promising materials for broadband and fast photodetection due to their gapless nature. Dirac heterostructures consisting of 2D Dirac semimetal graphene and its 3D analogue Cd3As2 should take the ascendency of high carrier mobility in both materials, while overcome the limitation of weak optical absorption in graphene-based devices and suppress the dark current occurring in pure Cd3As2 photodetectors. Herein, we report high-performance photodetectors based on a 3D Dirac semimetal Cd3As2/monolayer graphene heterostructure, which show broadband photoresponse from visible (488 nm) to mid-infrared (10 μm) wavelength region at room temperature without an external bias. The photodetectors are with a maximum responsivity of 0.34 mA/W at 488 nm and a fast response speed of ∼13 μs. In addition, the photoresponse can be enhanced by a gate voltage even in a long wavelength region. Our work suggests that the combination of the graphene and 3D Dirac semimetal is promising for high-performance photodetectors with broadband detection, high sensitivity, and rapid response.